The role of national platforms in charitable work (Ehsan platform as a model) Society of the Kingdom of Saudi Arabia - Al-Zahrani, Bashaier Abdullah (Journal of Humanities & Social Sciences, 2023)
This study explores an important social phenomenon since the existence of humanity based on helping members of society. It focused on the global technological development, which in turn led to facilitating all tasks, the most important of which is the establishment of a national platform for charitable work and government supervision to support the needy groups after studying their social status. This study, in specific, aims to identify the nature of the assistance provided by the Ihsan platform, the effects of the emergence of the Ihsan platform on charitable work, the obstacles that limit the work of the Ihsan platform, and finally the proposals that contribute to improving the level of the Ihsan platform. To achieve these goals, the study relied on the descriptive methodology and the questionnaire tool for data collection, which was conducted with a number of Ihsan platform beneficiaries who dealt with the Support Association in Jeddah, and it consisted of (107) items. Concerning the effects of the emergence of the Ihsan platform on charitable work, the results showed that the economic effects came in the first place, and that the establishment of the Ihsan platform helped in preventing manipulating the donors money. Finally, the study concluded with a set of recommendations, including the establishment of field headquarters for the Ihsan platform in the administrative areas to facilitate the access of beneficiaries to it, the preparation of an application that works on digital devices that facilitates the communication of beneficiaries with the officials of the Ihsan platform, and the development of a new program from the Ihsan platform for beneficiaries. They can attend educational courses that help them in the field of employment, in addition to conducting more sociological studies that deal with the internal work structure of the Ihsan platform (officials and operators) of the platform and also deal with the beneficiaries on a different and wide geographical scale.
Keywords: Benevolent Sociology; Social work; Charity work; Charities; National platforms; Saudi society